Land Tenure and Conservation in Chure - Singh, Bijay Kumar (Journal of Forest and Livelihood, 2017)
Covering about 13 per cent of the total land area of Nepal, Chure is an environmentally vulnerable, fragile and sensitive zone. Recognizing this, the Government of Nepal has declared it as “Chure Environmental Protection Area” and has formulated a high level board called “President Chure- Terai-Madhesh Conservation Board” to oversee the conservation activities in the region. Based on a review of literature and a decade long engagement of the author in the conservation in Chure, in this paper, I explore the status and issues related to the management of and land tenure in the Chure region. I find that land tenure is one of the most contested and challenging issues of conservation in Chure. With the presence of significant human settlements near to Chure Environmental Protection Area, the boundary is contested, particularly after the unilateral designation by the government; issues also remain around the rights to utilize forest resources. In fact, these factors have resulted in over exploitation of the resources, mainly by the upstream communities. I conclude the paper arguing for a broader, holistic approach that integrates upstream and downstream ecosystems in such a way that strengthens the historical socio-ecological links between the Chure region and the Terai so as to bring positive impacts for both.